Effect of Wedge Insertion Angle on Posterior Tibial Slope in Medial Opening Wedge High Tibial Osteotomy. Issue 2 (25th February 2016) - Ogawa, Hiroyasu; Matsumoto, Kazu; Ogawa, Takahiro; Takeuchi, Kentaro; Akiyama, Haruhiko
Background: Medial opening wedge high tibial osteotomy (HTO) is a well-established surgery for medial compartment knee osteoarthritis (OA) wherein the lower extremity is realigned to shift the load distribution from the medial compartment of the knee to the lateral compartment. However, this surgery is known to affect the posterior tibial slope angle (PTSA), which could lead to abnormal knee kinematics and instability, and eventually to knee OA. Although PTSA control is as important as coronal realignment, few appropriate measurements for this parameter have been reported. The placement of a wedge spacer might have an effect on PTSA. Purpose: To elucidate the relationship between the PTSA and the direction of insertion of a wedge spacer. Study Design: Case series; Level of evidence, 4. Methods: This study assessed 43 knees from 34 patients who underwent medial opening wedge HTO for knee OA. Pre- and postoperative lateral radiographs of the knee as well as postoperative computed tomography scans were performed to evaluate the relationship among PTSA, wedge insertion angle (WIA), and opening gap ratio (distance of the anterior opening gap/distance of the posterior opening gap at the osteotomy site). Results: The PTSA significantly increased from 9.0° ± 2.8° preoperatively to 13.2° ± 4.1° postoperatively ( P < .001), resulting in a mean ΔPTSA of 4.7° ± 4.5°. The mean opening gap ratio was 0.86 ± 0.11, and the mean WIA was 25.9° ± 8.4°. The WIA and opening gap ratio were both highly correlated with ΔPTSA ( r = 0.71 and 0.72, respectively), implying that a smaller WIA or smaller gap ratio leads to less increase in posterior slope. Conclusion: The direction of wedge insertion is highly correlated with PTSA increase, which suggests that the PTSA can be controlled for by adjusting the direction of wedge insertion during surgery. Clinical Relevance: Study results suggest that it is possible to adjust the PTSA by controlling the WIA during surgery. Proper attention to WIA can avoid an iatrogenic increase in posterior tibial slope.